Assessing the spatial and spatio-temporal distribution of forest species via bayesian hierarchical modeling - Rodríguez,de Rivera O; López-Quílez,A; Blangiardo,MAG (Forests, 2018)
Climatic change is expected to affect forest development in the short term, as well as the spatial distribution of species in the long term. Species distribution models are potentially useful tools for guiding species choices in reforestation and forest management prescriptions to address climate change. The aim of this study is to build spatial and spatio-temporal models to predict the distribution of four different species present in the Spanish Forest Inventory. We have compared the different models and showed how accounting for dependencies in space and time affect the relationship between species and environmental variables.